A measurement of Z(vv̄)[photon] cross section and limits on anomalous triple gauge couplings at [square root of]s = 7 TeV using CMS - Shrestha, Shruti (Kansas State University, 2013)
In this thesis, the first measurement of Z(vv̄)[photon] cross section in pp collisions at [square root of]s = 7 TeV has been done using data collected by the CMS detector. The measured cross section is 21.3 ± 4.2 (stat.) ± 4.3 (syst.) ± 0.5 (lumi.) fb. This measurement is based on the observations of events with missing transverse energy in excess of 130 GeV and photon in the rapidity range [eta] < 1.44 of transverse momentum in excess of 145 GeV in a data sample corresponding to an integrated luminosity of 5 fb⁻¹. This measured cross section is in good agreement with the theoretical prediction of 21.9 ± 1.1 fb from BAUR. Further, neutral triple gauge couplings involving Z bosons and photons have been studied. No evidence for the presence of such couplings is observed and is in agreement with the predictions of the standard model. We set the most stringent limits to date on these triple gauge couplings.
Keywords: Znunugamma cross section; Physics (0605)